Edukasi Pemanfaatan Tanaman Hidroponik kepada Siswa SMA AL-Khairat Kota Ternate, Maluku Utara - Astuti Amin (Cv. Utility Project Solution, 2023)
Students are the next generation of the nation who will have an essential role in realizing national food self-sufficiency and security. The condition of vacant land for farming in the Ternate City area is limited, so the fulfillment of basic food needs is obtained from outside Ternate Island. Understanding of hydroponic plants is also lacking. The purpose of this PkM activity is to educate Al-Khairat High School students in Ternate City, North Maluku to increase the use of limited land with hydroponic plants. The activity method is carried out in stages, covering the preparatory stage; discussion and coordination; hydroponic education; hydroponic planting; hydroponic placement; evaluation. Activities using lecture methods, interactive discussions, demonstrations, and work practices. Based on the results of the evaluation at the end of the PkM activity it was concluded that: (1) the enthusiasm of the activity participants was quite good, which was indicated by positive feedback such as questions and comments from participants; (2) the questionnaire level of participants' satisfaction with the activity was in the very good category (83.99%); and (3) the participants' level of understanding regarding hydroponic plants increased. This activity needs to be carried out in stages with a more intensive mentoring evaluation. The education process is expected to be carried out on a wider scope, not only in the school environment, but also in society as a whole.